Patrimoine des lycées d’Indre-et-Loire : de la collecte à la valorisation - Sébastien Chevereau; Isabelle Girard; Olga Yardin (In Situ)
Founded in 1807, the Lycée Descartes, a high school in Tours, epitomises two of the core missions carried out by the Departmental Archives, that is, the collection and promotion of the archival holdings of educational institutions. This article explores the interrelations between historical sources, dissemination and preservation of heritage.The Archives advises and supervises high school administrations regarding their historical records, such as the minutes of board meetings, rosters of students and teachers, but also class photographs and documents pertaining to movable heritage. Thankfully, the Lycée Descartes was able to preserve a large amount of historical records, antique books and pedagogical materials.With about 2 700 class photographs taken between 1895 and 2006, this high school kept alive a ritual born in the mid-nineteenth century. School pictures, a means of emphasising the value of public education and a boon for professional photographers, depict students, teachers and buildings, thus constituting a rich ethnological legacy. Touching both the institutional school environment and the privacy of the home, school photographs are ruled by legal considerations that need to be better defined so that we can make fuller use of this powerful cultural testimony. Antique instruments, belonging to several disciplines of physics and now part of the school’s heritage, have been catalogued and listed as historical artefacts. They were recently showcased in an exhibition. Their presence can be traced in the school’s records, and we should try to understand what light these sources can shed on all other actions carried out in the interest of preserving objects of historical value.